Physical Function and Health‐Related Quality of Life in Adults Treated With Asfotase Alfa for Pediatric‐Onset Hypophosphatasia. (4th August 2020) - Genest, Franca; Rak, Dominik; Petryk, Anna; Seefried, Lothar
ABSTRACT: Hypophosphatasia (HPP) is a rare, inherited, metabolic disease characterized by tissue‐nonspecific alkaline phosphatase deficiency resulting in musculoskeletal and systemic clinical manifestations. This observational study evaluated the effectiveness of enzyme replacement therapy with asfotase alfa on physical function and health‐related quality of life (HRQoL) among adults with pediatric‐onset HPP who received asfotase alfa for 12 months at a single center (ClinicalTrial.gov no.: NCT03418389). Primary outcomes evaluated physical function with the 6‐minute walk test (6MWT), timed up‐and‐go (TUG) test, Short Physical Performance Battery (SPPB), and handheld dynamometry (HHD). Secondary outcome measures included the Lower Extremity Functional Scale (LEFS), pain prevalence/intensity, and pain medication use; HRQoL was evaluated using the 36‐Item Short‐Form Health Survey version 2 (SF‐36v2). Safety data were collected throughout the study. All 14 patients (11 women) had compound heterozygous ALPL gene mutations and ≥1 HPP bone manifestation, including history of ≥1 fracture. Mean (min, max) age was 51 (19 to 78) years. From baseline to 12 months of treatment, median 6MWT distance increased from 267 m to 320 m ( n = 13; p = 0.023); median TUG test time improved from 14.4 s to 11.3 s ( n = 9; p = 0.008). Specific components of the SPPB also improved significantly: median 4‐m gait speed increased from 0.8 m/s to 1.1 m/s ( n = 10; p = 0.007) and median repeated chair‐rise time improved from 22 s to 13 s ( n = 9; p = 0.008). LEFS score improved from 24 points to 53 points ( n = 10; p = 0.002). Improvements in HHD were not clinically significant. SF‐36v2 Physical Component Score (PCS) improved after 12 months of treatment ( n = 9; p = 0.010). Pain level did not change significantly from baseline to 12 months of treatment. There were significant improvements on chair‐rise time and SF‐36v2 PCS by 3 months, and on TUG test time after 6 months. No new safety signals were identified. These results show the real‐world effectiveness of asfotase alfa in improving physical functioning and HRQoL in adults with pediatric‐onset HPP. © 2020 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.